The creative process : an ethnographic analysis - Berger, Arthur Asa, 1933- (Cambridge Scholars Publisher, 2021)
This fascinating and highly readable book, illustrated with many drawings by the author, uses semiotics, psychoanalytic theory, Marxist theory, and sociological theory to analyze creativity. It also includes short ""inserts"" by a communications scholar, a psychiatrist, a psychoanalyst, a semiotician, a humor scholar, and a media scholar offering their perspectives on the subject. The book relates creativity to humor, deals with the way Freud's and Marx's ideas can be applied to humor, and discusses many aspects of everyday life such as smart speakers, TikTok, hairstyles, bagels, and personal.
Keywords: Creative ability.; Creativity; Créativité.; creativity.; Interdisciplinary studies.; Semiotics -- semiology.; Cultural studies.; Creative ability